E-095 First-pass effect predicts clinical outcome and infarct growth after thrombectomy for distal medium vessel occlusions. (23rd July 2022) - Guenego, A; Lubicz, B
Abstract : Background and Purpose: The First Pass Effect (FPE) in endovascular thrombectomy (EVT) has been associated with better clinical outcomes and lower stroke progression in large-vessel-occlusion but has not been evaluated in distal, medium vessel occlusions (DMVOs). We sought to assess the impact on clinical outcome and stroke progression of the modified FPE (defined as a single-pass successful [mTICI 2b/2c/3] revascularization) in patients who underwent EVT for a primary DMVO. Methods: We collected the data of consecutive patients who underwent EVT for a primary DMVO in one large academic center and compared the rate of good clinical outcome (modified Rankin Scale of 0–2 at 3 months) and stroke progression between patients who achieved mFPE to non-mFPE patients. Results: Between January 2018 and January 2021, we included 60 patients who underwent an EVT for an acute ischemic stroke (AIS ) with a primary DMVO. Overall, mFPE was achieved in 32% (19/60) of EVT. mFPE was associated with a significantly higher rate of good clinical outcome compared to non-mFPE patients (89% versus 46%, ODDS ratio = 16.04 [2.23–115.39], p=0.006 in multivariate analysis). Final stroke volume was lower among mFPE patients (6.9mL [4.7–13.6] versus 23mL [14.6–47], p=0.001) as-well-as stroke progression (6.8mL [4–12.1] versus 17.8mL [8.1–34.9], p=0.016).mFPE was still associated with higher rates of good clinical outcome when compared to patients reaching an mTICI score ≥2b in more than one pass (89% versus 53%; ODDS ratio = 7.37 [1.43–38.08], p=0.017). Conclusion mFPE is associated with better clinical outcomes and lower stroke progression in DMVO. Disclosures: A. Guenego: None. B. Lubicz: None.